Ultrasonography and Fine‐Needle Aspiration in Indeterminate Thyroid Nodules: A Systematic Review of Diagnostic Test Accuracy. (19th August 2021) - Staibano, Phillip; Forner, David; Noel, Christopher W.; Zhang, Han; Gupta, Michael; Monteiro, Eric; Sawka, Anna M.; Pasternak, Jesse D.; Goldstein, David P.; de Almeida, John R.
Abstract : Objectives/Hypothesis: Sonographic risk criteria may assist in further prognostication of indeterminate thyroid nodules (ITNs). Our aim was to determine whether sonographic criteria could further delineate the post‐test probability of malignancy in ITNs. Study Design: Meta‐analysis of diagnostic test accuracy. Methods: A systematic review of Web of Science, MEDLINE, EMBASE, and CINAHL was performed from inception to April 15, 2021. Eligible studies included those which reported ultrasonographic evaluations with the American Thyroid Association (ATA) or the Thyroid Imaging Reporting and Data System (TIRADS) in adult patients with ITNs. ATA or TIRADS were scored as low (negative) or high (positive) malignancy risk using a previously validated binary classification. Primary outcomes included pooled sensitivity, specificity, likelihood ratios, and diagnostic odds ratio for all sonographic criteria. Studies were appraised using Quality Assessment of Diagnostic Accuracy Studies and the data were pooled using bivariate random‐effects models. Results: Seventeen studies were included in the analysis. For Bethesda III, ATA had a specificity (0.90, 95% confidence interval (CI): 0.74–0.94), but a sensitivity of 0.52 (95% CI: 0.25–0.77). Conversely, K‐TIRADS had the highest sensitivity (0.78, 95% CI: 0.62–0.89) with a specificity of 0.53 (95% CI: 0.31–0.74). Furthermore, American College of Radiology and EU TIRADS had specificities of 0.60 (95% CI: 0.36–0.80) and 0.81 (95% CI: 0.73–0.87) with sensitivities of 0.70 (95% CI: 0.37–0.90) and 0.38 (95% CI: 0.20–0.60), respectively. There were few studies with Bethesda IV nodules. Conclusions: Though dependent on malignancy rates, Bethesda III nodules with low‐suspicion TIRADS features may benefit from clinical observation, whereas nodules with high‐suspicion ATA features may require molecular testing and/or surgery. Level of Evidence: NA Laryngoscope, 132:242–251, 2022